Clostridium botulinum Type E Toxin: Effect of pH and Method of Purification on Molecular Weight - Sacks, Henry S. (1974)
The toxin of Clostridium botulinum type E was isolated from intact cells and from toxic culture filtrates by column chromatography at three pH values, 4.5, 5.3, and 6.0. At pH 6.0 and 5.3, the isolated toxin was in a form with a molecular weight (MW) of 86,000. This toxin was homogeneous on polyacrylamide gel electrophoresis and gel filtration and had an optical density ratio, 280 nm/260 nm, greater than 2.0. It did not dissociate at higher pH levels, but was dissociated into nontoxic components of approximately 12,000 MW when reduced and alkylated in the presence of 6 M guanidine hydrochloride. At pH 4.5, smaller amounts of an impure toxic moiety with a MW of 12,000 were found. After storage for 6 months, the 86,000-MW moiety had lost 60% of its lethality. Gel filtration revealed that the bulk of the toxicity was associated with a component having a MW of 150,000. Toxic components with MW of 12,000 and over 200,000 were also found. The toxin appears to polymerize or aggregate when in a pure form, so that most, if not all, of the MW previously reported for the toxin may belong to different polymers of a monomer with a MW of 12,000 or less. Treatment of the 86,000-MW toxin with trypsin resulted in an 18- to 128-fold increase in lethality, but no detectable change in MW.